Spain : Financial Sector Assessment Program; Technical Note; Housing Prices, Household Debt, and Financial Stability. (IMF Staff Country Reports; Country Report ;, 2006)
This report reviews the macroeconomic determinants of the rapid growth in the Spanish housing market, including various policy elements. It examines the vulnerabilities of households' finances as a result of the rapid growth of housing prices and mortgage debt. It also describes the Spanish mortgage market and assesses the resilience of the financial sector to a possible adjustment in the housing and mortgage markets. It presents a market-based indicator to show the market views on the quality of the mortgage portfolio and also provides recommendations.